Ajman University students’ perspectives on university social responsibility: A field study - Nagwa Babiker, Abdalla Yousif (Opción, 2019)
The aim of the study is to investigate Ajman university students’ perspectives on university social responsibility via a descriptive methodological approach, analyzing secondary data collated from selected existing Literature on USR that were related to the concept, origins, importance, and constraints of implementing of USR practices. The results indicate the extent to which students, as internal stakeholders, are aware of the USR, opportunities for its improvement, and its future challenges. In conclusion, no relationship existed between students’ academic grades and the USR and its role in the process of teaching, learning and dissemination of knowledge and the teaching of good citizenship.